1981
DOI: 10.1021/bi00513a015
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence lifetime and time-resolved polarization anisotropy studies of acyl chain order and dynamics in lipid bilayers

Abstract: The time-resolved fluorescence intensity and anisotropy decays of cis- and trans-parinaric acids and phosphatidylcholines labeled with trans-parinaric acid have been characterized in bilayers formed by several phosphatidylcholines and by dipalmitoylphosphatidylcholine-cholesterol mixtures, at several temperatures. Both a conventional free-running nitrogen flashlamp and the novel synchrotron source at the Stanford Linear Accelerator Center (SLAC) were used as excitation sources for a modified single photon coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
66
0

Year Published

1983
1983
2006
2006

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(77 citation statements)
references
References 50 publications
11
66
0
Order By: Relevance
“…The steady-state anisotropy, rs, is equivalent to [2p/(3 -p)] where p is the polarization. However, it should be noted that the steady-state anisotropy which is calculated according to Eqn ( 5 ) actually depends on both the rate and range of wobbling motion of the probe molecule, as well as on the fluorescence lifetime [41,43]. The steadystate anisotropy, rs, can be expressed as the sum of a kinetic term r b ( t ) and a static term, r W .…”
Section: Efject Of Ca2+ On Partitioning Of Probes Between Fluid and Smentioning
confidence: 99%
“…The steady-state anisotropy, rs, is equivalent to [2p/(3 -p)] where p is the polarization. However, it should be noted that the steady-state anisotropy which is calculated according to Eqn ( 5 ) actually depends on both the rate and range of wobbling motion of the probe molecule, as well as on the fluorescence lifetime [41,43]. The steadystate anisotropy, rs, can be expressed as the sum of a kinetic term r b ( t ) and a static term, r W .…”
Section: Efject Of Ca2+ On Partitioning Of Probes Between Fluid and Smentioning
confidence: 99%
“…We have followed up on this hypothesis by investigating the binding of parinaroyl-PI and parinaroyl-PC by use of time-resolved fluores-cence spectroscopy. This technique allows one to compare fluorescence lifeitmes, which are very sensitive to changes in environment [12], as well as fluorescence anisotropy decays which are a measure of acyl chain motion [13]. In a similar study on the binding of 1-parinaroyl-PC and 2-parinaroyl-PC to the PC-transfer protein from bovine liver it was demonstrated that each acyl chain was completely immobilized on the protein thereby occupying different binding sites [14].…”
Section: Introductionmentioning
confidence: 99%
“…The thickness of the DPH molecule approximates that of an acyl chain and its ordering in a membrane is presumed to reflect the order of the acyl chains [17], be it that the precise localization of the probe is unknown. The parinaroyl chromophore is relatively rigid (carbon atoms 9-16) and its movement will depend not only upon the movement and order of the surrounding acyl chains but also on depolarizing motions of the acyl chain in which it is present [16]. Cholesterol increases mainly the order of the first 8-10 carbon atoms of the phospholipid acyl chains [411.…”
Section: Izrythrocytesmentioning
confidence: 99%
“…As a first approach the measurement of the steady-state fluorescence anisotropy (rs) was carried out. It has been shown that in case of DPH [12][13][14][15], parinaric acid and PnPC [16] anisotropy values are determined by two components: The residual anisotropy (too) which is related to the order parameter of the probe and a dynamic term (rf) which depends upon the apparent rotational correlation time and the fluorescence life time of the probe [17]. The relation between these factors has been discussed in detail by van Blitterswijk et al [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation